Effects of prenatal diagnostic ultrasound exposure on rabbit fetus: in vivo physical and morphological changes - Md Dom, Sulaiman; Ahmad Zaiki, Farah Wahida (LAP LAMBERT Academic Publishing, 2018)
Ultrasound is extensively used in various clinical specialities since it was perceived to lack in bioeffects. In obstetrics and gynaecology, it has been proven useful in fetal assessment and abnormalities. Due to high sensitivity of developing fetus to external interferences, through diagnostic ultrasound advances, the revision of potential prenatal bioeffects is needed to be corroborated. This in-vivo experimental study was designed to determine the physical and morphological effects on fetus development. Twelve pregnant rabbits were exposed to ultrasound exposure durations of 30, 60 and 90 minutes in the middle of three stipulated gestational stages. All other acoustic output parameters were kept constant throughout the study. Total 136 foetuses; group O: n=31, A: n=35, B: n=31, and C: n=39 were analysed. One-way ANOVA showed significant differences in foetal weight at the 1st stage and 3rd stage exposed for 90 minutes (P=0.01 and 0.05 respectively), and at the 2nd stage exposed for 60 minutes (P=0.01). Pearson correlation showed negative correlations between exposure durations and foetal weight at the 1st and 3rd stage (P=0.02 and 0.04 respectively), while Simple Linear Regression showed significant linear relationship. For brain volume and surface, significant differences found in brain volume and surface at the 2nd stage exposed for 60 and 90 minutes, and at the 3rd stage exposed for 60 minutes. No significant linear relationship found between exposure durations and brain volume and surface at all stages. Result suggested that prenatal ultrasound exposure might interfere with those sensitive stages hence, plausibly interrupted the physical development. Further work is needed to provide more scientific evidences on prenatal ultrasound effects on foetus.